PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD PADA MATERI OLIMPIADE MATEMATIKA - Silitonga, R H Yanti (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
The research was carried out to determine the improvement of elementary students' mathematical problem solving skills with Olympic material after training using the guided discovery method. The research subjects were 26 students of SD AL-Hilal Kamal. The average result of the students' pretest was 19 while the average result of the posttest of students was 54. The average increase in students' mathematical problem solving abilities was 35. Student responses to this training were very positive based on the number of student attendance, namely 100%